IMPLEMENTASI ETIKA BISNIS ISLAM DALAM MARKETTING TOKO AUSATH MART PUTRA PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Annas, Mohamad; Mawardi, Sumari; Mun’im, Munif (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study aims to determine the implementation of Islamic business ethics in the marketting of the Ausath Mart Putra Store at the Darussalam Blokagung Banyuwangi Islamic Boarding School. The results showed that the application of Islamic business ethics at the Ausath Mart were: 1) Honest, the delivery made from the Ausath Mart Putra to the board of the boarding school and board of the boarding school to the head of the hostel then the head of the hostel conveyed to the residents of the hostel without adding any lies. 2) Amanah, the delivery is conveyed correctly and not by force. 3) Fatanah, conveying to the board of boarding schools and pesantren administrators to the head of the hostel then the head of the hostel conveyed to the residents of the dormitory, this shows that the intelligence of the Ausath Mart Putra unit in developing its business is only promoting without spending money but has a very large effect in improving sales results. 4) Tabligh, all delivery is done properly and correctly in accordance with what was said at the beginning and not detrimental to either party.